THE EFFECT OF COLLABORATIVE STRATEGIC READING (CSR) ON STUDENTS’ READING COMPREHENSION AT ISLAMIC SENIOR HIGH SCHOOL - Adila, Rima; Eliza Trimadona; Uyun Nafiah (JR-ELT (Journal of Research in English Language Teaching), 2023)
The purpose of this study was to determine the effect of Collaborative Strategic Reading (CSR) on studentsâ€™ reading comprehension in class X MA Al-Khairiyah Tanjung Jabung Barat and to find out the significant difference between students who were taught with CSR and those who were not. This research is quantitative research with quasi experimental designusing total sampling. The population and research sample were class X IPK and X IPS MA Al-Khairiyah Tanjung Jabung Barat. Total population was 44 students. In sampling 22 students in the experimental class and 22 students in the control class. Quasi experiment has been applied in this study with the design of 2 groups pre-test and 2 group post-test. The result of this study show that there is a significant effect on studentsâ€™ reading comprehension after being taught using CSR. This result can be seen from the T-test which show average value of the experimental class pre-test is 54.73 and the average of the control class pre-test is 51.82 while the average value of the control class post test is 63.82 and the average of the experimental class post test is 74.18 higher than the pre-test is 54.73. In the paired sample T-test result sig (2-tailed)0,000 is smaller than 0.05 this proves ð»ð‘Ž is accepted while the independent sample test result sig (2-tailed) is 0,002 < 0.05 it means that there is a significant difference. The researcher concluded that using Collaborative Strategic Reading can improve studentsâ€™ reading comprehension and there is a significant difference betwen student who are taught with CSR and student who are not taught with CSR.